Casos de dengue, leptospirose e meningite na cidade de Belém - PA e sua correlação com as variáveis meteorológicas no período de 1999 a 2009 - SILVA, Helder José Farias da (2019)
This study was developed as part of Biometeorology, field of knowledge consisting of the biological effects of weather and climate of the physicochemical environment in living organisms, plants, animals and man. Dengue is now the most important arbovirus (arthropod-borne disease) that affect humans and constitutes a serious public health problem worldwide, especially in tropical countries, where environmental conditions favor the development and proliferation of Aedesaegypti, the principal mosquito. Bethlehem atmospheric conditions favor the action of the mosquito vector to transmit the dengue virus, providing more rapid proliferation and weather elements considered in the research work on the incidence Dengue in Bethlehem in the range of 54%. Leptospirosis is a zoonosis that still has a high incidence in the Amazon, resulting in a high hospital costs, and loss of working days and its lethality, which can reach up to 40% of severe cases. The seasonality of leptospirosis in the city of Belem-Pa was evident, proving that the disease is directly proportional to rainfall, so the highest incidence of the disease occur in the first five months of the year (the period with highest rainfall) and inversely proportional to temperature. The term meningitis expresses the occurrence of an inflammation of the meninges, the membranes surrounding the brain, meningitis may be caused by various infectious agents like bacteria, viruses and fungi, among others, and non-agents infection (eg: trauma). The main vector and the man in the case of tuberculous meningitis, other animals, especially cattle, can be reservoirs of the disease. The development of meningitis was associated mild to moderate meteorological elements studied cases of meningitis. It appears that the minimum temperature, precipitation, relative humidity and air temperature are correlated on only one, 34, 41 and 46% (weak correlation), respectively, of cases of meningitis, and the maximum temperature greater association with features 62% (moderate correlation), therefore a higher coefficient of explanation of it on to meningitis. The degree of correlation of these pathologies with the meteorological elements, were around weak to moderate positive / negative, explaining that in addition to meteorological factors pathologies are related to other factors such as socio-environmental, nutritional, poor sanitary conditions and overpopulation.